Biological therapeutics - Greenstein, Ben, 1941-; Brook, Daniel A. (London : Pharmaceutical Press, 2011)
This introductory textbook covers all the main categories of biological medicines, including vaccines, hormonal preparations, drugs for rheumatoid arthritis and other connective tissue diseases, drugs developed from older cytotoxic approaches and discusses the development of newer drugs and future developments.
Includes bibliographical references and index.
Keywords: Biological Agents